Adapted Motivational Interviewing to Promote Exercise in Adolescents With Congenital Heart Disease: A Pilot Trial. Issue 4 (October 2018) - McKillop, Adam; Grace, Sherry L.; Ghisi, Gabriela Lima de Melo; Allison, Kenneth R.; Banks, Laura; Kovacs, Adrienne H.; Schneiderman, Jane E.; McCrindle, Brian W.
Abstract : Purpose: To assess a motivational interviewing (MI) intervention to improve moderate-to-vigorous physical activity (MVPA) in adolescents with congenital heart disease. Methods: Intervention participants received one-on-one telephone-based adapted MI sessions over 3 months. Outcomes were acceptability, change mechanisms (stage of change and self-efficacy), and limited efficacy (physical activity, fitness, and quality of life). Results: Thirty-six participants were randomized. Intervention participants completed 4.2 ± 1.2/6 MI sessions, with no improvements in the high self-efficacy or stage of change observed. Participants accumulated 47.24 ± 16.36 minutes of MVPA/day, and had comparable outcomes to peers without heart disease (except for functional capacity). There was no significant difference in change in any outcome by group. Conclusions: The intervention was acceptable, but effectiveness could not be determined due to the nature and size of sample. Clinical Relevance: Pediatric cardiac rehabilitation remains the sole effective intervention to increase MVPA in this population. Abstract : Supplemental Digital Content is Available in the Text.To assess a motivational interviewing intervention to improve moderate-to-vigorous physical activity in adolescents with congenital heart disease.